2008
DOI: 10.1002/tt.61
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of wear properties of different Fe‐based hardfacing alloys in four kinds of testing methods

Abstract: Iron-based hardfacing alloys are widely used to protect machinery equipment. A strong correlation is given between microstructure and chemical composition of welding deposit with the resulting wear behaviour. Concerning precipitation of metallurgical hard phases and synthetic added hard particles, the bonding strength of the hard phases in the metallic matrix seems to play a dominating role to obtain high wear resistance. The main objective of this study was to evaluate the wear behaviour for pure abrasion, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Surprisingly, material D with the highest hard phase content does not perform better than material B at higher temperatures; the worse matrix backup at high temperatures leads to bigger breakouts, which increases the wear. Due to a finer microstructure and better matrix-carbide interfacial bonding, investigated earlier [13], material C does not suffer from this wear increase at higher temperatures that much. Both the ductile materials A and B form composite layers at high temperatures (Fig.…”
Section: Ht-ciat Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, material D with the highest hard phase content does not perform better than material B at higher temperatures; the worse matrix backup at high temperatures leads to bigger breakouts, which increases the wear. Due to a finer microstructure and better matrix-carbide interfacial bonding, investigated earlier [13], material C does not suffer from this wear increase at higher temperatures that much. Both the ductile materials A and B form composite layers at high temperatures (Fig.…”
Section: Ht-ciat Results and Discussionmentioning
confidence: 93%
“…Mechanical and abrasive wear properties of the alloys depend on their microstructure and chemical composition [1][2][3][4][5][6][7][8][9][10][11][12]. To achieve impact resistance, a good ductility and good interfacial carbide-matrix bonding is necessary [13]. Therefore, for high-impact application, martensitic materials are best suited [14].…”
Section: Introductionmentioning
confidence: 99%
“…Fe-Cr-C alloys are well known for their excellent performances under severe wear conditions [4], [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These hardfacing materials usually contain molybdenum, which can withstand high temperatures (Wang et al 2008). Other works (Arikan et al 2001;Bedolla-Jacuinde et al 2005;Badisch et al 2008) show possibility of titanium for the development of TiC in microstructure hardfacing. These studies showed that titanium carbide (TiC) formation into hardfacing increases abrasive resistance more than hardfacing containing NbC.…”
mentioning
confidence: 99%
“…Some studies (Radulovic et al 1994;Badisch et al 2008) also highlight that increasing of volume fraction of eutectic carbides influenced toughness negatively. One of the ways for developing relatively toughness hardfacing is the use of fine grains of eutectic colonies.…”
mentioning
confidence: 99%